COMPARISON BETWEEN COAGULATION PROFILE IN NEWBORNS OF NORMAL PREGNANCY, PREECLAMPSIA AND ECLAMPSIA PATIENTS. A CROSS-SECTIONAL STUDY. - Singh, Randhir; Singh, Maya; Jaiswal, Ritika (Student’s Journal of Health Research Africa, 2024)
Introduction Preeclampsia involves endothelial dysfunction, poor placentation, vasospasm, and hematological changes. These lead to a hypercoagulable state, exacerbated in preeclampsia-eclampsia. Neonates born to hypertensive mother face risks including growth retardation, thrombocytopenia, and other complications, potentially resulting in severe neonatal issues like DIC and serious hemorrhage. Aim The aim of this study was to assess and compare the coagulation parameters between newborns born to women who had pre-eclampsia and eclampsia, and those born to normotensive mothers who were healthy and did not have any medical conditions. Material and method Present study was a cross-sectional study undertaken from June 2023 to May, 2024. 100 neonates were included in both the study and control group were on Day 1 of birth. Neonates born to mothers with eclampsia, pre-eclamptic toxemia, and gestational hypertension were further classified into the test category. Results A noteworthy association was noted between reductions in fetal age and modifications in every coagulation parameter. As PIH severity increased, there was a significant lengthening in partial thromboplastin time with kaolin (PTTK) and thrombin time (TT) values, as well as an increased risk of prematurity and hyperbilirubinemia. Preterm infants had a greater incidence of dissemination of intravascular coagulation (DIC) than mature neonates. Conclusion Pregnancy-related hypertension directly affects the unborn child of the affected woman, changing the coagulation parameters and increasing the neonate’s risk of bleeding from a decreased platelet count and a compromised coagulation profile. It has been discovered that preterm babies are more affected than term babies. Because of all these findings, this neonate group needs excellent prenatal care, resuscitation facilities, and regular monitoring of their clotting status.